The Extent to Which the Brainstorming Strategy Contributes to the Development of Educational Competencies from the Point of View of Teachers - A Field Study in the First Cycle Schools in Lattakia City – - ونوس, ميس; هيام زريقي ,; مهند مبيض , (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to know the extent of the contribution of the brainstorming strategy to the development of educational competencies among a sample of teachers of the first cycle of basic education from their point of view in Lattakia city. To achieve the goal of the research, the descriptive analytical method was used, and the sample included (206) teachers in the schools of the first cycle of basic education in Lattakia for the academic year (2022/2023). A questionnaire was designed that included five skills, namely (planning skill, implementation skill, evaluation skill, communication skill), and these areas included (30) phrases. The research reached a set of results, the most important of which are: - The overall degree of the contribution of the brainstorming strategy and its role in developing the educational competencies of the teachers of the first cycle of basic education in the schools of the city of Lattakia was high, with an arithmetic mean of (3.72), and a relative importance of (74.4%). - The field of planning first, with an arithmetic average of (3.96), and a relative importance of (79.2%). The field of implementation ranked came in the second place, with an arithmetic mean of (3.78), and a relative importance of (75.6%), with a high degree, also evaluation ranked third, with an arithmetic mean of (3.7), and a relative importance of (74%), with a high degree for three fields. - The field of communication came in the fourth place, with an arithmetic mean of (3.4), and a relative importance of (68%), with a medium degree.